2003
DOI: 10.1021/jo034480z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Octahydroquinolines through the Lewis Acid Catalyzed Reaction of Vinyl Allenes and Imines

Abstract: The reaction of vinyl allenes with imines under Lewis acid catalysis has been explored. Vinyl allenes in which the allenic portion of the molecule is tri- or tetrasubstituted gave octahydroquinoline derivatives as single isomers together with a minor compound formed by an ene reaction of the imine with the allene. Compounds in which the allene is 1,3-disubstituted do not react under the conditions assayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…When these semicyclic vinylallenes were reacted with Nbenzylimines, the adducts with an octahydroquinoline skeleton were obtained as a single isomer with cis-stereochemistry in each case (Equation 1). 3 The yields were similar to those obtained in the reaction with aldehydes.…”
Section: Equationsupporting
confidence: 74%
“…When these semicyclic vinylallenes were reacted with Nbenzylimines, the adducts with an octahydroquinoline skeleton were obtained as a single isomer with cis-stereochemistry in each case (Equation 1). 3 The yields were similar to those obtained in the reaction with aldehydes.…”
Section: Equationsupporting
confidence: 74%
“…While the optimal conditions for cycloaddition of tetrasubstituted vinylallenes 3 and 5 were found to involve heating overnight at 50–60 °C, the less substituted allene 9 required heating at 80 °C for 8 h to achieve complete reaction (entry 3). The success of this cycloaddition is noteworthy as Palenzuela reported that vinylallene 9 fails to undergo the Diels–Alder reaction with N -benzylimines in the presence of Lewis acids . Application of the cycloaddition/isomerization strategy to vinylallenes lacking substituents at the allene terminus provides access to pyridines bearing methyl substituents (entries 4 and 5), and in the case of the phenyl-substituted substrate 11 , base treatment was not necessary as the initial cycloadduct isomerized to pyridine 16 under the conditions of the cycloaddition.…”
Section: Resultsmentioning
confidence: 99%
“…To introduce the methyl group and the allene functionality, alcohol 11 was transformed into methyl carbonate 12 . The propargylic carbonate of 12 was treated with Gilman’s reagent9 to produce the trisubstituted allene 13 10. The allene compound 13 was treated with tetrabutylammonium fluoride to give the primary alcohol 14 .…”
Section: Resultsmentioning
confidence: 99%